PENGUJIAN BERBAGAI AKTIVITAS EKSTRAK AIR ROSELLA SECARA IN VITRO (HIBISCUS SABDARIFFA L.) - Malinda, Okta; Syakdani, Adi (Politeknik Negeri Sriwijaya, 2021)
Roselle (Hibiscus sabdariffa L.) is a plant that is often found in various countries and one of them is in Indonesia. The purpose of this review is to find out more about the activity of rosella water extract by testing in vitro. Roselle water extract is more commonly used compared to ethanol roselle extract. The activity of roselle water extract that has been found by in vitro testing is neuroprotective, antioxidant, antidiabetic, melanoma inhibitor, antibacterial, antihypertensi immune response, adipogenesis inhibitor, apoptosis inhibitor and modulation of MCP-1 production.